Broadcasting and Accessibility Services Currently Offered for Deaf and Hard of Hearing Viewers by Catalan-language Broadcasters - Irene Tor-Carroggio; Sara Rovira-Esteva (Revista Mediterránea de Comunicación, 2019)
This article presents the main results of a user-centered study which seeks to provide an overview of accessibility services for the deaf and hard of hearing on offer from a representative sample of Catalan-language broadcasters. The study had three objectives. First, to analyze the type of accessibility services offered, basically captions and Catalan Sign Language interpreting, both in linear broadcasts and video-on-demand services. Second, to determine the volume of accessibility services offered and to what extent they comply with the law. Finally, to assess users’ experience, focusing on their level of satisfaction with the current offer and on their opinions with regard to new possibilities that could lead to improving accessibility services. Combining a qualitative and quantitative approach has enabled us to triangulate data to afford not only a holistic picture of the situation, but also to suggest actions for improvement.